2019
DOI: 10.2147/ppa.s196224
|View full text |Cite
|
Sign up to set email alerts
|

<p>South Asians&rsquo; experience of managing hypertension: a grounded theory study</p>

Abstract: Objective We examined the process that South Asians undergo when managing their hypertension (HTN). Method Using grounded theory methods, 27 community-dwelling English-, Punjabi-, or Hindi-speaking South Asian participants (12 men and 15 women), who self-identified as having HTN were interviewed. Transcripts were analyzed using constant comparison. Results The core category was “fitting it in”. First, the participants assessed their diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Thus, It can be seen that the daily management of hypertension in western developed countries is mainly concentrated in the community, with the community as the main prevention and control to implement the management of chronic diseases such as hypertension [23]. The models of community management of hypertension in some countries mainly include chronic disease care model, chronic disease self-management model, continuous nursing model, peer support management model [24]. In the community, doctors, nurses, pharmacists and other team members use clinical information systems to provide evidence-based decision support for patients, and ultimately improve patients' self-management ability [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, It can be seen that the daily management of hypertension in western developed countries is mainly concentrated in the community, with the community as the main prevention and control to implement the management of chronic diseases such as hypertension [23]. The models of community management of hypertension in some countries mainly include chronic disease care model, chronic disease self-management model, continuous nursing model, peer support management model [24]. In the community, doctors, nurses, pharmacists and other team members use clinical information systems to provide evidence-based decision support for patients, and ultimately improve patients' self-management ability [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The models of community management of hypertension in some countries mainly include chronic disease care model, chronic disease self-management model, continuous nursing model, peer support management model [ 24 ]. In the community, doctors, nurses, pharmacists and other team members use clinical information systems to provide evidence-based decision support for patients, and ultimately improve patients' self-management ability [ 24 , 25 ]. In addition to doctors, the team also emphasizes that nurses and pharmacists are involved in the management of high blood pressure as health care managers.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence is a well-recognized factor affecting hypertension control, involving patient’s regular use of medications, adherence to a modified diet plan and lifestyle changes ( 167 , 168 ). Multiple studies have reported that a high percentage of hypertensive South Asian patients (33–67.6%) remain non-adherent to their medications ( 21 ). A population-based cohort study found, after adjustment for patient and clinical factors, South Asian and Chinese individuals had significantly lower adherence compared with White individuals ( 169 ).…”
Section: Awareness and Adherencementioning
confidence: 99%
“…Hypertension does seem to follow a more aggressive path in the South-Asian population (18,19). Their chances of being hypertensive at a younger age are nearly three times greater than European whites (20,21). However, evidence over whether hypertension is more common in South-Asians is ambiguous (22,23).…”
Section: Epidemiologymentioning
confidence: 99%
“…A qualitative study on challenges faced by South Asian migrants observed a lack of understanding in how to access relevant self-management resources. 13 Although disaggregated data among South Asian subgroups is limited, 14 prior research has demonstrated that Asian Americans are less likely than the average population to have their BP checked (74% versus 83%, respectively). 15 Primary care practices also face challenges in supporting the needs of South Asian patients, including ability to offer culturally-and linguistically-appropriate health coaching on chronic disease management, 16 which may result in a diminished capacity to identify, manage, and refer South Asian hypertensive patients to appropriate BP management resources.…”
mentioning
confidence: 99%